2019
DOI: 10.3390/s19245533
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Emotional Responses to Photographs and Artwork Using a Deep Learning-Based Approach

Abstract: Visual stimuli from photographs and artworks raise corresponding emotional responses. It is a long process to prove whether the emotions that arise from photographs and artworks are different or not. We answer this question by employing electroencephalogram (EEG)-based biosignals and a deep convolutional neural network (CNN)-based emotion recognition model. We employ Russell’s emotion model, which matches emotion keywords such as happy, calm or sad to a coordinate system whose axes are valence and arousal, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
(29 reference statements)
0
16
1
Order By: Relevance
“…Classic artistic media, such as pencil or watercolor brush, produce similar effects. It is also notable to invoke the conclusion of the work of Yang et al’s work [ 38 ] that the artwork images induce higher valence than photographs. Since the illustrated surgical image can be regarded as a kind of artwork, the increased valence for the illustrated surgical image reinforces the conclusion of [ 38 ].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Classic artistic media, such as pencil or watercolor brush, produce similar effects. It is also notable to invoke the conclusion of the work of Yang et al’s work [ 38 ] that the artwork images induce higher valence than photographs. Since the illustrated surgical image can be regarded as a kind of artwork, the increased valence for the illustrated surgical image reinforces the conclusion of [ 38 ].…”
Section: Discussionmentioning
confidence: 92%
“…The independent decisions from the modules were merged using a voting strategy to make a final decision. Their model was trained and optimized using DEAP dataset, and applied to distinguish the emotional responses between photographs and artwork images [ 38 ] and to verify the influence of contrast on valence [ 39 ].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They compared their performance with the existing studies and showed better accuracy for valence and arousal. They also extended their emotion recognizer to apply the task of distinguishing emotional responses to photographs and artwork [19].…”
Section: Deep Learning-based Modelsmentioning
confidence: 99%
“…Deep learning is a particularly popular research method nowadays. It can learn the internal laws and representation levels of sample data through multi-layer neural networks, and it has been widely used in many fields in recent years [ 38 , 39 , 40 , 41 , 42 , 43 ]. At the same time, neural networks are also considered as a useful method for unsteady aerodynamic modeling.…”
Section: Artificial Neural Network Modelsmentioning
confidence: 99%